Use of Magnetic Nanoparticles as Targeted Therapy: Theranostic Approach to Treat and Diagnose Cancer - Arif Malik; Tariq Tahir Butt; Sara Zahid; Fatima Zahid; Sulayman Waquar; Mahmood Rasool; Mahmood Husain Qazi; Aamer Mahmood Qazi (Journal of Nanotechnology)
The metastasis of cancer epitomizes the diagnostic and therapeutic challenge as a result of cancer heterogeneity. To overcome the uncontrolled growth of the proliferating cells, nanosystems have been developed and have undergone many preclinical trials both in vitro and in vivo and many practices have been further applied clinically on human beings. In practice, magnetic nanoparticles- (MNPs-) based systems following the application of Fe3O4 bound antitumor drug have shown an enhanced therapeutic index in comparison with conventional chemotherapy ensuring the significant decline in nanosystems’ toxicity. A number of improved strategies employing nanoparticle engineering have been in practice for upgrading selectivity of metastatic cells and to have direct access to poorly manageable tumor regions. Targeted nanoparticle therapy paving the way towards tumor biomarkers and tissue specific cancer stages provides effective strategies for nonaccessible tumor regions, thus leading to the tangible modification in the history of cancer world. An infinite number of targets have been exploited for surface receptor specificity to distinct types of nanoparticles and are presently enduring clinical practices both in vitro and in vivo. The aim of this review is to take into view current nanotechnology-based research in cancer imaging for diagnosis and treatment. Several commercially available magnetic nanoparticles-based systems applied as contrast agents for metastatic cancer imaging and treatment via hyperthermia have also been focused on.